To whom and why F. M. Dostoevsky is precious? - Charota, Ivan A. (Journal of the Belarusian State University. Sociology, 2021)
The article is devoted to the analysis of F. M. Dostoevsky’s work regarding his 200th anniversary. The author aims to reveal to whom and why the great writer and thinker is precious, and how his work is perceived in Serbia. He tries to evaluate what contributes to and what hinders the comprehension of the F. M. Dostoevsky phenomenon. The author notes that veneration for such a writer can be fully expressed when everyone who has mastered literacy starts reading at least one of his works and feels the field of attraction and repulsion, which does not always correlate with the problem field of scientific F. M. Dostoevsky studies. Unfortunately, the author states that the youth do not initially develop an elementary desire to necessarily be included in the literary classics in such conditions when the entire system of basic education seems to be subordinated to the task of discouraging any desire to read on their own, and even more so to feel and reflect. Interest in «Crime and punishment» is almost impossible to arouse basing on stereotypical comments with a retelling of the plot, some elements of which are included in the tests for the subject devoid of attractiveness. And the plot, moreover, is fully conveyed by the half-page versions of the novel, which are prepared by enterprising interpreters precisely for passing the test as the optimal form of attestation. At the same time, the judgments of foreign writers are used surprisingly widely, and at the same time thoughtlessly – the main thing is that they have an appropriate image. Over time, it becomes more and more obvious that few contemporary writers can compare to F. M. Dostoevsky both in the depth and completeness of ideas about the real life of a Russian person, especially in the scope of its spheres, and in the insight of the analysis of everything that happened and which inevitably followed from what was happening. For a century and a half, F. M. Dostoevsky has remained an unparalleled bearer of the conscience of mankind, a kind of seismograph of the coming upheavals. The author states that in Serbia, the reverent perception of F. M. Dostoevsky, which was formed under the influence of the Russian religious emigration, dominates. A separate topic is also the impressive activity and productivity of the Serbian scientific F. M. Dostoevsky studies. Finally, if all this we project onto the Belarusians, then it would be appropriate to say that F. M. Dostoevsky is the bearer of special patriotism manifested not in superficial pathos, which usually serves either self-praise or complacency, but in soberly analytical and constructive criticism, which presupposes, first of all, self-criticism, as an indispensable component of sound national self-awareness.